Quantum physics for dummies - Holzner, Steven, 1957- (--For dummies., 2013)
Quantum physics-- also called quantum mechanics or quantum field theory-- can be daunting for even the most dedicated enthusiast of science, math, or physics. This plain-English guide makes the micro world understandable and accessible, and it's packed with fully explained examples to help you tackle the tricky equations like a pro!